KUALITAS BAGASE TEBU (SACCHARUM OFFICINARUM L) MELALUI BIOPROSESSING MENGGUNAKAN PROBIOTIK - Sri Rahayu; Subagyo Subagyo (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2023)
The aims of the study was to determine the nutritional quality of fermented sugarcane bagasse using probiotics. The study were design with completely randomized design (CRD) with 4 treatments and 4 replications. The treatments used were: A0 = 0% A1 = 2.5%, A2 = 5% and A3 = 7.5% and the fermentation time used was 30 days. The data obtained was analyzed for variance (Anova). Parameters observed were dry matter, ash, crude protein, crude fiber and crude lipid. Based on the results of this study, fermented sugarcane bagasse had a significant effect (P<0.05) on dry matter, ash, crude protein, crude fiber and had no effect on (P>0.05)crude lipid fermented sugarcane bagasse. The best treatment was obtained at A3 then followed by A2, A1 and A0. The dry matter content was 92.82%, the ash content was 1.33%, the crude protein was 3.89%, the crude lipid content was 0.52% and the crude fiber content was 31.99%.